In Vivo and In Vitro Methods to Identify DNA Sequence Variants that Alter RNA Splicing. (26th April 2018) - Patel, Parth N.; Gorham, Joshua M.; Ito, Kaoru; Seidman, Christine E.
Abstract: Identification of sequence variants that create or eliminate splice sites has proven to be a significant challenge and represents one of many roadblocks in the clinical interpretation of rare genetic variation. Current methods of identifying splice‐altering sequence variants are limited by an imperfect understanding of splice signals and the need for cumbersome functional assays. We have recently developed a computational tool that prioritizes putative splice‐altering sequence variants and a moderate‐throughput minigene assay that confirms the variants that alter splicing. This bioinformatic strategy represents a substantial increase in accuracy and efficiency with respect to historical in vitro splicing assays. In this article, we give detailed instructions on how to organize, run, and interpret various features of this procedure. We expect that splice‐altering variants revealed through this protocol can be reliably carried forward for further clinical and biological analyses. © 2018 by John Wiley & Sons, Inc.